Atta Halilintar : Agen Strukturisasi Karir Generasi-Z - Reza Praditya Yudha (Universitas Serang Raya, 2020)
The development of technology and media have been integrated in society to individuals lives. Everyone can have access and skills to use technology to become a prosumer, producer as well as consumer of media content. Technology then transforms roles, needs, and social systems. This includes reconstructing definitions of career, professionalism, and even success. The reconstruction process is not easy, not necessarily, and cannot be carried out by just any individual. Someone needs to be an agent who integrates resources and consistently applies rules. This study uses literature study method to analyze agents who have succeeded in changing the social structure, Atta Halilintar. By basing on the thought of the Giddens’ Structuration Theory, the researcher examines the elements of resources that are owned by Atta and his consistency applying the rules. It is not easy to be an agent who is able to change the structure of a social system. Discipline, flexibility, and having strong principles are the keys to Atta utilizing technology and media, to become pioneers who are able to redefine the meaning of career, professionalism, and success in the digital age.